2015
DOI: 10.1364/oe.23.027509
|View full text |Cite
|
Sign up to set email alerts
|

WS_2 saturable absorber for dissipative soliton mode locking at 106 and 155 µm

Abstract: Transition-metal dichalcogenides, such as tungsten disulfide (WS2) and molybdenium disulfide (MoS2), are highly anisotropic layered materials and have attracted growing interest from basic research to practical applications due to their exotic physical property that may complement graphene and other semiconductor materials. WS2 nanosheets are found to exhibit broadband nonlinear saturable absorption property, and saturable absorbers (SAs) are fabricated by depositing WS2 nanosheets on side-polished fibers. Att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
84
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 195 publications
(87 citation statements)
references
References 56 publications
2
84
1
Order By: Relevance
“…As well as traditional mechanisms based on nonlinear polarisation evolution (NPE) arising from the Kerr effect in the fibers [2] various external materials have been harnessed to create the required fast switches in such cavities, such as semiconductor saturable absorber mirrors (SESAMs [3,4] or, more recently, saturable absorbers based on two dimensional materials suchg as MoS 2 and graphene [5][6][7][8][9][10]). While some recent research has focussed on polarisation-maintaining (PM) fiber cavities [11], a large number of cavities have continued to use non-PM fibers and with NPE as a fast saturable absorber, either in combination with a SESAM or, as here, acting in tandem with a spectral filter.…”
Section: Introductionmentioning
confidence: 99%
“…As well as traditional mechanisms based on nonlinear polarisation evolution (NPE) arising from the Kerr effect in the fibers [2] various external materials have been harnessed to create the required fast switches in such cavities, such as semiconductor saturable absorber mirrors (SESAMs [3,4] or, more recently, saturable absorbers based on two dimensional materials suchg as MoS 2 and graphene [5][6][7][8][9][10]). While some recent research has focussed on polarisation-maintaining (PM) fiber cavities [11], a large number of cavities have continued to use non-PM fibers and with NPE as a fast saturable absorber, either in combination with a SESAM or, as here, acting in tandem with a spectral filter.…”
Section: Introductionmentioning
confidence: 99%
“…Defects may also explain observations of SA at sub-bandgap photon energies in TMD flakes grown using CVD [30,34]; however, the role of edges may be less significant due to typically larger flake sizes. Other crystallographic defects, such as vacancies and grain boundaries, could contribute to sub-bandgap absorption, as verified by numerical simulations in both MoS 2 [58,59] and WS 2 [53].…”
Section: Origin Of Sub-bandgap Saturable Absorptionmentioning
confidence: 59%
“…However, recent work has shown that all-normal and net-normal dispersion maps, producing dissipative solitons, can enable higher pulse energies [1,74]. Such designs have also been exploited for TMD-based mode-locked fibre lasers [33,44,45,53].…”
Section: Mode-locked Fibre Lasersmentioning
confidence: 99%
“…The fiber-based SA is formed by sandwiching the CNT film between two facets of a fiber connector, and the nonlinear absorption property of the SA is measured with a balanced twin-detector technique. 35 As demonstrated in Figure 2(b), the optical transmission increases with the intensity of the illuminating pulse and becomes saturated at a certain value, which is the representative property of SAs. 36 Through fitting the result with a common model, 37 the saturable intensity and modulation depth of the SA are given as 8.6 MW/cm 2 and 3.3%, respectively.…”
mentioning
confidence: 89%